How Effective are Policy Interventions Against the COVID-19 Infection Rates? - Chor Foon Tang; Bee Wah Tan (Faculty of Economic and Business, 2023)
Studies on the COVID-19 pandemic are more likely to concentrate on the effects of the virus while ignoring its time-series characteristics, particularly its stationarity characteristics. Thus, this study attempts to investigate the effectiveness of policy interventions against COVID-19 by determining the permanent or transitory effects in 5 major regions and the ten most infected countries. Using the endogenous multiple breaks unit root tests introduced by Kapetanios (2005), the findings indicate that only the impacts of shocks to COVID-19 infection rates in France are likely to be permanent. However, the transitory effect is found in Brazil, Germany, Iran, Italy, Russia, Spain, Turkey, the United Kingdom, and the United States. The country where the shock has a permanent impact is suitable for policy interventions, including lockdowns, social isolation, and local isolation. While herd immunity, which protects the entire population against COVID-19, is better ideal for application in countries that experience shocks with a transitory effect.JEL Classification: C1, I15, I18How to Cite:Tang, C.F., & Tan, B.W. (2023). How Effective are Policy Interventions Against the COVID-19 Infection Rates? Etikonomi, 22(1), 1–14. https://doi.org/10.15408/etk.v22i1.28486.